Subretinal implantation of a monolayer of human embryonic stem cell-derived retinal pigment epithelium: a feasibility and safety study in Yucatán minipigs - Koss, Michael Janusz (Graefe's archive for clinical and experimental ophthalmology, 2016)
A subretinal implant termed CPCB-RPE1 is currently being developed to surgically replace dystrophic RPE in patients with dry age-related macular degeneration (AMD) and severe vision loss. CPCB-RPE1 is composed of a terminally differentiated, polarized human embryonic stem cell-derived RPE (hESC-RPE) monolayer pre-grown on a biocompatible, mesh-supported submicron parylene C membrane. The objective of the present delivery study was to assess the feasibility and 1-month safety of CPCB-RPE1 implantation in Yucatán minipigs, whose eyes are similar to human eyes in size and gross retinal anatomy.
Gesehen am 22.05.2020